A Study on Transparency in Software Development Projects From the Perspective of Project Managers - Sampaio, Lucas Tito; Vieira, Jeferson Kenedy Morais; Farias Junior, Ivaldir Honório de (Anais do Simpósio Brasileiro de Sistemas de Informação (SBSI); 2025: Anais do XXI Simpósio Brasileiro de Sistemas de InformaçãoDO - 10.5753/sbsi.2025.246403, 2025)
Context: Transparency is a fundamental concept for projects and their management, as this attribute can enhance trust, communication, stakeholder engagement, risk management, accountability, adaptability, and performance monitoring. Problem: The scarcity of studies on transparency in software projects hinders its implementation and limits the understanding of stakeholders’ needs, resulting in poor communication and a negative impact on project success. Solution: In order to improve the understanding of transparency in software development, the study aims to understand how project managers conceptualize and assess the relevance of transparency in software projects, as well as to identify the mechanisms used to promote it. Information Systems Theory: This work was developed based on Stakeholder Theory, which highlights the need for organizations to consider the expectations of all impacted groups. The study addresses how transparency influences these stakeholders and its relevance in group engagement. Method: This study adopts a qualitative and exploratory approach. A total of 12 interviews were conducted with guests holding management positions in the software field, which were analyzed using Bardin’s Thematic Analysis. Summary of Results: The interview codes were divided into four groups that highlight the study’s objectives: "Transparency Assessment," "Transparency Conceptualization," "Challenges Faced," and "Tools, Mechanisms, and Practices." Within these groups, there are 46 categories, which encompass a total of 399 codes. Contributions and Impact in the area of Information Systems: This article contributes to a better understanding of transparency in the context of software project management. Consequently, it is possible to explore better ways to implement it, thereby promoting trust and informed decision-making among stakeholders.